Chromatic Schultz and Gutman Polynomials of Jahangir Graphs J2,m and J3,m - Ramy Shaheen; Suhail Mahfud; Qays Alhawat (Journal of Applied Mathematics)
Topological polynomial and indices based on the distance between the vertices of a connected graph are widely used in the chemistry to establish relation between the structure and the properties of molecules. In a similar way, chromatic versions of certain topological indices and the related polynomial have also been discussed in the recent literature. In this paper, we present the chromatic Schultz and Gutman polynomials and the expanded form of the Hosoya polynomial and chromatic Schultz and Gutman polynomials, and then we derive these polynomials for special cases of Jahangir graphs.